2022
DOI: 10.1002/srin.202200094
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Ti Content on the Grain Stability and the Recrystallization Behavior of Nb‐Alloyed High‐Strength Low‐Alloyed Steels

Abstract: To achieve higher strength and good hardenability and at the same time use the positive effects of thermomechanical controlled processing, the concept of Nb and Ti microalloyed steels is increasingly used for high‐strength low‐alloy (HSLA) steels with higher C contents. Herein, how the addition of Ti affects the grain growth and static recrystallization behavior of a Nb microalloyed HSLA steel with a C content of 0.23 wt% is investigated. For this reason, alloys with varying Ti and constant Nb content are prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In particular, CT is known to have Metals 2024, 14, 249 2 of 17 a strong effect on nano-scale precipitates [19][20][21][22][23]. For Nb-Ti HSLA pipeline steel, Nb and Ti play a significant role in achieving their strength [3,24], as the precipitation of Nb and Ti is very sensitive to CT [19,20]. For Nb-Ti micro-alloyed steel, the precipitates begin to form at a CT of 675 • C. The intermediate precipitates are small in size and randomly distributed in the matrix at a CT of 650 • C [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, CT is known to have Metals 2024, 14, 249 2 of 17 a strong effect on nano-scale precipitates [19][20][21][22][23]. For Nb-Ti HSLA pipeline steel, Nb and Ti play a significant role in achieving their strength [3,24], as the precipitation of Nb and Ti is very sensitive to CT [19,20]. For Nb-Ti micro-alloyed steel, the precipitates begin to form at a CT of 675 • C. The intermediate precipitates are small in size and randomly distributed in the matrix at a CT of 650 • C [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…For Nb-Ti HSLA pipeline steel, Nb and Ti play a significant role in achieving their strength [3,24], as the precipitation of Nb and Ti is very sensitive to CT [19,20]. For Nb-Ti micro-alloyed steel, the precipitates begin to form at a CT of 675 • C. The intermediate precipitates are small in size and randomly distributed in the matrix at a CT of 650 • C [20][21][22][23][24][25]. During the coiling process in TMCP, large (Nb, Ti)C particles and small spherical (Nb, Ti)C particles form in Nb-Ti HSLA pipeline steel, which leads to dislocation pinning [21].…”
Section: Introductionmentioning
confidence: 99%
“…This process, through plastic deformation at high temperatures, enables the material to achieve the desired geometric shape and size. Simultaneously, the internal microstructure of the material undergoes a complex evolution, including recrystallization, grain growth, and phase transformation [ 5 , 11 , 14 , 15 ]. Scientific research has shown that fine control of hot-rolling parameters, such as the heating temperature, degree of deformation, deformation speed, and cooling rate, can manipulate the material’s microstructure at the microscopic level, thus achieving targeted performance design at the macroscopic scale [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…High-strength microalloyed steel (HSLA) is widely utilized as the main material for offshore platforms, offshore wind power generation, and other marine engineering equipment based on its high strength, high toughness, and excellent fatigue properties [1][2][3]. Conventional HSLA steels are mainly alloyed with alloying elements such as Nb, Ti, and Cr to improve the strength and plasticity of the materials.…”
Section: Introductionmentioning
confidence: 99%